2003
DOI: 10.1089/104454903321112442
|View full text |Cite
|
Sign up to set email alerts
|

ORP3 Splice Variants and Their Expression in Human Tissues and Hematopoietic Cells

Abstract: ORP3 is a member of the newly described family of oxysterol-binding protein (OSBP)-related proteins (ORPs). We previously demonstrated that this gene is highly expressed in CD34(+) hematopoietic progenitor cells, and deduced that the "full-length" ORP3 gene comprises 23 exons and encodes a predicted protein of 887 amino acids with a C-terminal OSBP domain and an N-terminal pleckstrin homology domain. To further characterize the gene, we cloned ORP3 cDNA from PCR products and identified multiple splice variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…AB014604). This ORP3 cDNA encodes a protein which corresponds to ORP3 isoform 1a (AAM27386) (Collier et al 2003). Human ORP6 (AF323728) and ORP7 (AF323729) cDNAs were also cloned from HuH7 cell line as described earlier (Lehto et al 2001).…”
Section: Cdna Constructsmentioning
confidence: 99%
See 3 more Smart Citations
“…AB014604). This ORP3 cDNA encodes a protein which corresponds to ORP3 isoform 1a (AAM27386) (Collier et al 2003). Human ORP6 (AF323728) and ORP7 (AF323729) cDNAs were also cloned from HuH7 cell line as described earlier (Lehto et al 2001).…”
Section: Cdna Constructsmentioning
confidence: 99%
“…1). The ORP3-N cDNA encodes a protein (445 aa), which is 197 amino acids shorter than ORP3 isoform 2a (AAM27390) (Collier et al 2003). All constructs were verified by cycle sequencing (BIGDYE) and an automated ABI377 sequencer (Applied Biosystems).…”
Section: Cdna Constructsmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological study: Epidemiological studies of ORP1S or ORP2 are not reported yet. (Collier, Gregorio-King et al 2003). In human tissues there was specific isoform distribution, with most tissues expressing varied levels of isoforms with the complete ORD; while only whole brain, kidney, spleen, thymus, and thyroid expressed high levels of the isoforms associated with the truncated ORD.…”
Section: Osbpl1a (Orp1s) and Osbpl2 (Orp2)mentioning
confidence: 97%